2019
DOI: 10.1097/dss.0000000000001922
|View full text |Cite
|
Sign up to set email alerts
|

WHO Surgical Checklist in Dermatology: Compliance, Barriers, and Attitudes

Abstract: BACKGROUND The World Health Organization (WHO) surgical checklist is associated with reduced morbidity and mortality. Efficacy correlates with compliance. OBJECTIVE This study aims to (1) establish completion rate and (2) identify and address barriers to use. METHODS Records of patients undergoing dermatological surgery were studied. Staff completed attitude and barriers questionnaires. Checklist process was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…8 The factors influencing the success of, and barriers faced following, implementation are multifactorial. 20 For example, lack of time, 21 education or training delivery 21,22 and crucially, human behaviour factors. 23 Thus, the attitudes of veterinary professionals (VPs) towards SSCs will be a key determinant that influences frequency and manner of use, and consequently, SSC introduction success.…”
Section: Introductionmentioning
confidence: 99%
“…8 The factors influencing the success of, and barriers faced following, implementation are multifactorial. 20 For example, lack of time, 21 education or training delivery 21,22 and crucially, human behaviour factors. 23 Thus, the attitudes of veterinary professionals (VPs) towards SSCs will be a key determinant that influences frequency and manner of use, and consequently, SSC introduction success.…”
Section: Introductionmentioning
confidence: 99%
“…Tian, et al . [ 16 ] stated that even these safety checks were performed, 24% of the checklist items may still be missed. Aveling, et al [ 17 ] observed that although medical staff could realize or appreciate the value of this checklist, they also felt puzzled or dissatisfied with its implementation, which related to conflicts between their philosophical background, local culture, medical education conditions, and social/economic factors.…”
Section: Introductionmentioning
confidence: 99%